Ferrostalderite, CuFe2TlAs2S6, a new mineral from Lengenbach, Switzerland: occurrence, crystal structure, and emphasis on the role of iron in sulfosalts. (2nd January 2018) - Biagioni, Cristian; Bindi, Luca; Nestola, Fabrizio; Cannon, Ralph; Roth, Philippe; Raber, Thomas
Abstract: The new mineral species ferrostalderite, CuFe2TlAs2S6, was discovered in the Lengenbach quarry, Binn Valley, Wallis, Switzerland. It occurs as minute, metallic, black, equant to prismatic crystals, up to 50 mu;m, associated with dolomite, realgar, baumhauerite (?) and pyrite. Minimum and maximum reflectance data for COM wavelengths in air are [λ (nm): R (%)]: 471.1: 24.2/25.4; 548.3: 23.7/24.7; 586.6: 22.9/23.8; 652.3: 21.0/22.0. Electron microprobe analyses give (wt.%): Cu 6.24(25), Ag 4.18(9), Fe 9.95(83), Zn 4.46(91), Hg 1.22(26), Tl 26.86(62), As 19.05(18), Sb 0.63(6), S 25.39(47), total 97.98(72). On the basis of 12 atoms per formula unit, the chemical formula of ferrostalderite is Cu0.75(2) Ag0.30(1) Fe1.36(10) Zn0.52(11) Hg0.05(1) Tl1.00(1) [As1.94(4) Sb0.04(1) ]∑1.98(4) S6.04(4) . The new mineral is tetragonal, space group I4̄2 m, with a = 9.8786(5), c = 10.8489(8) Å, V = 1058.71(11) Å 3, Z = 4. The main diffraction lines of the calculated powder diagram are [d (in Å), intensity, hkl]: 4.092, 70, 211; 3.493, 23, 220; 3.396, 35, 103; 3.124, 17, 310; 2.937, 100, 222; 2.656, 19, 321; 2.470, 19, 400; 2.435, 33, 303. The crystal structure of ferrostalderite has been refined by Xray single-crystal data to a final R1 = 0.050, on the basis of 1169 reflections with F0 > 4σ(F0). It shows a three dimensional framework of (Cu, Fe)-centred tetrahedra (1M1 + 2 M2), with channels parallel to [001] hosting disymmetric TlS6 and (As, Sb)S3 polyhedra. Ferrostalderite is derived from its isotype stalderite M1 Cu M2 Zn2 TlAs2 S6 through the homovalent substitution M2Zn2+ → M2Fe2+. The ideal crystal-chemical formula of ferrostalderite is M1 Cu M2 Fe2 TlAs2 S6 .